Managing democratization: Achievements and limitations in AK Party era - Babacan, Abdurrahman (SETA Foundation, 2019)
During its first two terms (2002-2012), AK Party adopted a range of constitutional democratization reforms connected with the EU accession process covering issues such as: freedom of thought, faith, expression and assembly, the legal and practical improvements regarding the Kurdish issue, opening process on the Alevite question, a new libertarian stress and vision on minority rights, and diminishing, even eliminating, the prerogatives of the military. Nevertheless, since 2013 there have been big challenges triggered both by internal and external developments, which have caused a rippled path for democratization. This paper aims to provide a comprehensive documentation on the question of democratization on the one hand and a holistic assessment and perspective of the current situation, on the other.
Keywords: AK Party; democratization